2020
DOI: 10.1002/gps.5268
|View full text |Cite
|
Sign up to set email alerts
|

The generalizability of Older Adult Self‐Report (OASR) syndromes of psychopathology across 20 societies

Abstract: Objectives As the world population ages, psychiatrists will increasingly need instruments for measuring constructs of psychopathology that are generalizable to diverse elders. The study tested whether syndromes of co‐occurring problems derived from self‐ratings of psychopathology by US elders would fit self‐ratings by elders in 19 other societies. Methods/design The Older Adult Self‐Report (OASR) was completed by 12 826 adults who were 60 to 102 years old in 19 societies from North and South America, Asia, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…When considered by syndrome, the median OABCL item loadings ranged from 0.47 for Worries to 0.77 for Functional Impairment, indicating large‐item loadings for each syndrome. Our findings were consistent with previous findings for the OASR, a parallel self‐report questionnaire, whose syndrome structure was supported in 19 societies, in addition to the United States (Ivanova et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When considered by syndrome, the median OABCL item loadings ranged from 0.47 for Worries to 0.77 for Functional Impairment, indicating large‐item loadings for each syndrome. Our findings were consistent with previous findings for the OASR, a parallel self‐report questionnaire, whose syndrome structure was supported in 19 societies, in addition to the United States (Ivanova et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…As far as we know, this was only the second study in which the generalizability of syndromes of older adult psychopathology was tested across multiple societies. The first study was conducted by Ivanova et al (2020), who tested the fit of the United States 7‐syndrome model derived from self‐ratings on the OASR to self‐ratings by 12,826 60‐ to 102‐year‐olds in 19 societies. Their results supported the OASR syndrome structure across the tested societies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, as Mindt, et al (2019), there is currently a scarcity of assessment instruments that are common between cultures, linguistically diverse and that measure psychopathological constructs and psychosocial competencies in people specifically over 60 years of age. To overcome this limitation, the Achenbach questionnaires are instruments capable of evaluating the clinical, sociodemographic and psychosocial competencies of older people, and it has recently been reported that the empirical syndromes of the Older Adult Self-Report (OASR) questionnaire (Achenbach et al, 2004), are generalizable to 19 different societies in America, Europe and Asia (Ivanova et al, 2020). The existing correlations between the empirical syndromes measured by the questionnaire have a positive and high magnitude among them, the highest correlation being the irritability / disinhibition syndrome with thought problems (rxy = .90), thought problems with anxiety / depression (rxy = .86), and memory / cognition problems with functional impairment (rxy= .82) (Ivanova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the genetic architecture of psychopathology appears to consist of sets of genetic influences operating at different levels of specificity, across a multi-tiered hierarchy. For example, models using genetic loci identified in genome-wide association studies (GWAS) found that a significant proportion of genomic influences is common to numerous psychiatric disorders (e.g., schizophrenia, depression, attention-deficit/hyperactivity disorder) 4,5 . The remaining risk, which is considerable in size, is disorder-specific, indicating that genetic factors unique to narrow constructs also play a role in the etiology of psychopathology.…”
Section: The Utility Of Hierarchical Models Of Psychopathology In Genmentioning
confidence: 99%
“…Nearly all of their references are based on Anglophone samples. Rather than being added as an afterthought, multicultural studies of the structure, prevalence, and other aspects of psychopathology should be fundamental components of ongoing research on hierarchical models 5,6 .…”
mentioning
confidence: 99%